Development of computational algorithm for multicomponent liquid phase using adsorption in a fixed bed using method of lines - Hernandez, Jovy L. (2009)
A numerical algorithm is developed to calculate breakthrough curves from mathematical multicomponent adsorption models. The calculated breakthrough curves are compared with experimental data found in a lifetime. The numerical algorithm is developed using the Method of Lines. The adsorption equations used are those proposed by Hsieh, et al. who considered the effect of liquid and solid resistances as they pertain to three cases: liquid phase controlling, solid phase controlling and neither phase controlling. The algorithms developed and implemented into a computer program using MathCAD (ver. 1.4) software is able to solve the mathematical problem in considerably less time compared to the characteristics Method. The results using the Method of Lines are comparable with the values obtained by Hsieh, et al. using the characteristics Method. The breakthrough curves generated using the mathematical multicomponent adsorption models shows expected trend and approximate results but deviate from the experimental data due to some factors not accounted in the model equations. The effluent concentrations and the adsorption rate using the model equations are higher as compared to the experimental data. This significant deviation from the experimental data is due to the assumptions associated with the derivation of model equations such as Langmuir equilibrium isotherm and no axial dispersion are too restrictive and does not fully describe the system used in the experiment.